The Representation of the Prophet in the Qur’an and Sīrah: A Historiographical Critique of the Narrative of the Prophet’s Life in Ibn Isḥāq’s Sīrah Nabawiyyah - Rosyadi, Lalu Imron; Muhibbi, Moh. Saddad; Umam, Habiibul; Jannah, Mutia Miftachul; Fallah, Muhammad Noor (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The reconstruction of the historical life of Prophet Muhammad has predominantly relied on classical sīrah narratives, which are often apologetic in nature, while the Qur’an—as a contemporaneous document—has frequently been overlooked in historiographical inquiries. This article addresses three central questions: (1) How is the Prophet Muhammad represented in the Qur’an in comparison to the sīrah? (2) Are there narratives in the sīrah that contradict or diverge from the Qur’anic representation? and (3) What are the methodological implications of using the Qur’an as a critical tool in examining classical Islamic historiography? By employing a textual-comparative approach to selected key narratives in Ibn Isḥāq’s Sīrah Nabawiyyah alongside relevant Qur’anic verses, this article demonstrates that the Qur’an portrays the Prophet primarily as a human figure grappling with the challenges of his mission—distinct from the heroic and overly miraculous image often found in the sīrah. In several cases, the sīrah appears to contradict the ethos and content of the Qur’an. This article argues that the Qur’an should not be viewed merely as a supplementary source but as a legitimate and authoritative means of internal critique of the sīrah, thereby offering a new methodological pathway for studying the Prophet’s life in a more historical, critical, and balanced manner.